Peter the Great - Abbott, Jacob, 1803-1879 (Salt Lake City, UT : Project Gutenberg, 2007)
"Peter the Great" by Jacob Abbott is a historical account written in the late 19th century. The book chronicles the life and reign of Peter the Great, focusing on his rise to power, his efforts to modernize Russia, and the political intrigues that shaped his rule. It aims to offer readers insight into the transformative period of Russian history led by this significant figure. At the start of the narrative, the reader is introduced to the complex familial dynamics within the Russian royal family, particularly the rivalry between Peter and his half-sister, Sophia. Following the death of their father, tensions rise as Peter, still a child, is proclaimed emperor, while Sophia maneuvers for power, employing espionage and manipulation to maintain her influence. The opening sets the stage for Peter's emergence as a strong leader against the backdrop of conspiracy and political strife, foreshadowing his future struggles and the monumental changes he would bring to Russia. (This is an automatically generated summary.)
Release date is 2007-06-21
E-text prepared by Al Haines
Keywords: Peter I, Emperor of Russia, 1672-1725; Russia -- History -- Peter I, 1689-1725